A fast and secure key-value service using hardware enclaves - Messadi, Ines; Neumann, Shivananda; Almstedt, Lennart; Kapitza, Rüdiger (Middleware Demos and Posters 2019 - Proceedings of the 2019 20th International Middleware Conference Demos and Posters, Part of Middleware 2019, 2019)
Trusted execution as offered by Intel Software Guard Extensions (SGX) enables confidentiality and integrity for cloud-hosted services. While in principle all kinds of workloads can be secured using trusted execution, key-value stores have gained special attention as these services are an essential building block of most complex cloud deployments. So far the main design challenge has been to address current performance limitations of SGX. In addition, we identify the integration of SGX-guarded workloads with recent network technology, especially Remote Direct Memory Access (RDMA) as an upcoming requirement. RDMA allows fast direct access to remote memory at high bandwidth. However, SGX protected memory cannot be directly accessed over the network. Furthermore, due to the more powerful network, secured services might likely be CPU-bound as a result of the necessary cryptographic operations. In this paper, we present a new key-value store architecture that utilizes trusted execution to offer confidentiality and integrity, while using RDMA for low latency and high bandwidth communication. To prevent a server-side CPU bottleneck, clients pre-compute cryptographic operations when possible while data movement in and out of the trusted execution environment has been reduced to the bare minimum.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Intel SGX; Key-value storage; Remote Direct Memory Access

Precursor: A fast, client-centric and trusted key-value store using RDMA and Intel SGX - Messadi, Ines; Neumann, Shivananda; Weichbrodt, Nico; Almstedt, Lennart; Mahhouk, Mohammad; Kapitza, Rüdiger (Middleware 2021 - Proceedings of the 22nd International Middleware Conference, 2021)
As offered by the Intel Software Guard Extensions (SGX), trusted execution enables confidentiality and integrity for off-site deployed services. Thereby, securing key-value stores has received particular attention, as they are a building block for many complex applications to speed-up request processing. Initially, the developers' main design challenge has been to address the performance barriers of SGX. Besides, we identified the integration of a SGX-secured key-value store with recent network technologies, especially RDMA, as an essential emerging requirement. RDMA allows fast direct access to remote memory at high bandwidth. As SGX-protected memory cannot be directly accessed over the network, a fast exchange between the main and trusted memory must be enabled. More importantly, SGX-protected services can be expected to be CPU-bound as a result of the vast number of cryptographic operations required to transfer and store data securely. In this paper, we present Precursor, a new key-value store design that utilizes trusted execution to offer confidentiality and integrity while relying on RDMA for low latency and high bandwidth communication. Precursor offloads cryptographic operations to the client-side to prevent a server-side CPU bottleneck and reduces data movement in and out of the trusted execution environment. Our evaluation shows that Precursor achieves up to 6 - 8.5 times higher throughput when compared against similar SGX-secured key-value store approaches.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Intel SGX; key-value stores; RDMA

SplitBFT: Improving Byzantine Fault Tolerance Safety Using Trusted Compartments - Messadi, Ines; Becker, Markus Horst; Bleeke, Kai; Jehl, Leander; Mokhtar, Sonia Ben; Kapitza, Rüdiger (Middleware 2022 - Proceedings of the 23rd ACM/IFIP International Middleware Conference, 2022)
Byzantine fault-tolerant agreement (BFT) in a partially synchronous system usually requires 3f + 1 nodes to tolerate f faulty replicas. Due to their high throughput and finality property, BFT algorithms build the core of recent permissioned blockchains. As a complex and resource-demanding infrastructure, multiple cloud providers have started offering Blockchain-as-a-Service. This eases the deployment of permissioned blockchains but places the cloud provider in a central controlling position, thereby questioning blockchains' fault tolerance and decentralization properties and their underlying BFT algorithm. This paper presents SplitBFT, a new way to utilize trusted execution technology (TEEs), such as Intel SGX, to harden the safety and confidentiality guarantees of BFT systems, thereby strengthening the trust in could-based deployments of permissioned blockchains. Deviating from standard assumptions, SplitBFT acknowledges that code protected by trusted execution may fail. We address this by splitting and isolating the core logic of BFT protocols into multiple compartments resulting in a more resilient architecture. We apply SplitBFT to the traditional practical byzantine fault tolerance algorithm (PBFT) and evaluate it using SGX. Our results show that SplitBFT adds only a reasonable overhead compared to the non-compartmentalized variant.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Byzantine Fault Tolerance; Intel SGX; Safety

SURESOFT: Towards Sustainable Research Software - Blech, Christopher; Dreyer, Nils; Friebel, Björn; R. Jacob, Christoph; Shamil Jassim, Mostafa; Jehl, Leander; Kapitza, Rüdiger; Krafczyk, Manfred; Kürner, Thomas; C. Langer, Sabine; Linxweiler, Jan; Mahhouk, Mohammad; et al. (2022)
Researchers develop software to process or generate data to test their scientific hypotheses. Especially researchers from STEM disciplines (Science, Technology, Engineering, and Mathematics) validate their models through self-developed software prototypes. However, they do not necessarily have a programming or software engineering background. Moreover, scientific software development happens in a time-constrained environment focusing on the fast publication of results. In addition, as scientists usually have limited contracts, the software is developed with short-term goals in mind. Therefore, the resulting software is mostly rapidly developed and contains code artifacts that are hard to maintain, extend and even reproduce due to missing documentation or dependencies. These factors, among others, hinder researchers from progressing and further developing their software. Thus, research software sustainability is vital to the research process to ensure that software can be evolved and reused by the next generation of scientists. To foster sustainability, scientists can highly benefit from education in principles and practices of software engineering, which can further be supported by established methods, tools, and technologies. This paper introduces SURESOFT, a twofold approach to address challenges in the development of research software regarding sustainable science that combines tools and infrastructure with education in the form of workshops and training. Furthermore, we report our experience of applying the SURESOFT approach to five software projects from different fields and discuss challenges, such as common bad practices and applicability in diverse scenarios. </

TEE-Assisted Recovery and Upgrades for Long-Running BFT Services - Messadi, Ines; Gerber, Markus Elias; Distler, Tobias; Kapitza, Rüdiger (Proceedings of the 20th International Conference on Availability, Reliability and Security (ARES '25), 2025)

Towards Low-Latency Byzantine Agreement Protocols Using RDMA - Schwarz-Rüsch, Signe; Messadi, Ines; Kapitza, Rüdiger (Proceedings - 48th Annual IEEE/IFIP International Conference on Dependable Systems and Networks Workshops, DSN-W 2018, 2018)
Byzantine fault tolerance (BFT) protocols can mitigate attacks and errors and are increasingly investigated as consensus protocols in blockchains. However, they are traditionally considered costly in terms of message complexity and latency due to the required multiple rounds of message exchanges. With the availability of Remote Direct Memory Access (RDMA) in data centers, message exchange latency can be reduced compared to TCP, as RDMA enables kernel bypassing and thereby avoids intermediate data copying. Retaining the performance benefits for RDMA during its integration, however, is non-trivial and error-prone. While the use of RDMA has previously been explored for key/value stores, databases and distributed file systems, agreement protocols especially for BFT have so far been neglected. We investigate the usage of RDMA in the Reptor BFT protocol for low-latency agreement and show first steps towards an RDMA-enabled consensus protocol. For this, we present Rubin, a framework offering similar functionality to the Java NIO selector, which can handle multiple network connections efficiently with a single thread and is employed in several BFT protocol implementations such as BFT-SMaRt and UpRight.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Blockchain Consensus; Byzantine Fault Tolerance; Remote Direct Memory Access

ZugChain: Blockchain-Based Juridical Data Recording in Railway Systems - Schwarz-Rüsch, Signe; Bleeke, Kai; Messadi, Ines; Schmidt, Stefan; Krampf, Andreas; Olze, Katharina; Stahnke, Susanne; Schmid, Robert; Pirl, Lukas; Kittel, Roland; Polze, Andreas; Franz, Marquart; et al. (Proceedings of the 52nd International Conference on Dependable Systems and Networks, 2022)
In modern trains, a juridical recording unit logs events that occur during operation. This data is used to reconstruct the exact chain of events in case of failures and crashes. To ensure data recovery after an accident, the recorder is hardened against physical damage and secured against tampering; however, it is a single proprietary device and by no means indestructible. This paper presents ZugChain, a distributed, blockchain-based juridical recording unit that opportunistically utilizes on-train hardware. ZugChain offers high reliability via replication and tamper-resistance due to the nature of blockchains. It implements a permissioned blockchain based on a Byzantine fault-tolerant agreement protocol suitable for diverse communication systems. To utilize the logged data for advanced services, e. g., predictive maintenance, ZugChain securely and continuously exports traces to private data centers. We demonstrate ZugChain's feasibility with an implementation running on real train hardware, where we show that ZugChain orders data within 14 ms using at maximum 15 % of the total available shared CPU resources, thus fulfilling requirements of juridical recorder
Keywords: railway; BFT; event recorder; blockchain